Tailoring functionality and durability of polymeric products by modifying processing conditions - Florjančič, Urška (Strojniški vestnik, 2008)
We investigate new possibilities for modifying functionality of polymeric products by changing their material structure during processing and consequently their time-dependent properties, which define the durability of final products. In the first part of the paper we report on significant differences in material structure as observed at atomistic scale due to differences in processing conditions. A short overview of recent studies on multi-scale phenomena in material structure formation is included. Several experimental approaches are proposed for studying the effect of processing conditions on material structure formation and hence, the macroscopic properties of the final polymeric product. ...
Keywords: polimeri; predelava; struktura; lastnosti; funkcionalnost